From Classical Terrorism to ‘Global’ Terrorism - Wieviorka, Michel (International Journal of Conflict and Violence (IJCV), 2007)
This article examines the history and the development of terrorism as a research subject for social sciences. It gives an impression of how the subject’s theoretical remit has changed over the last decades — explicitly taking into account the characteristics of a modern and global world and their impact on current understandings of terrorism. Terrorism is a minor object for the social sciences; it was even long considered “illegitimate” and neglected by researchers. There are several explanations for this, which I think my long experience in research authorizes me to evoke here.